Effects of a sedentary behavior reduction intervention on common cardiometabolic risk factors in metabolic syndrome patients : a three-month randomized controlled trial - Garthwaite, Taru (2020)
Sedentary behavior is associated with metabolic disorders, cardiovascular disease, type 2 diabetes, and premature mortality. However, evidence regarding the health effects of sedentary behavior relies mainly on findings from observational epidemiological studies, experimental trials, or interventions of a short duration, and the understanding of causal cardiometabolic benefits of sitting time reductions in long term is lacking. The purpose of this three-month intervention study was therefore to investigate whether reducing sedentary behavior could improve the cardiometabolic health in subjects at high risk for cardiometabolic diseases.